Optical characteristics and parameters of gas-discharge plasma on mixtures of mercury dichloride vapor and neon - Malinina, A.A.; Hrytsak, R.V. (Вопросы атомной науки и техники, 2019)
The results of studies of the optical characteristics and parameters of DBD (dielectric barrier discharge) plasma on a mixture of mercury dichloride vapor, neon are presented. The following functions were established: EEDF, transport characteristics, specific discharge power losses on electronic processes, electrons’ concentration and temperature, rate constants for elastic and inelastic electron scattering on components of the working mixture, depending on the E/N. Представлено результати досліджень оптичних характеристик і параметрів газорозрядної плазми бар'єрного розряду на суміші парів дихлориду ртуті і неону. Встановлено: ФРЕЕ, транспортні характеристики, питомі втрати потужності розряду на електронні процеси, концентрація і температура електронів, константи швидкостей процесів пружного і непружного розсіювання електронів на компонентах робочої суміші в залежності від величини приведеної напруженості електричного поля. Представлены результаты исследований оптических характеристик и параметров газоразрядной плазмы барьерного разряда на смеси паров дихлорида ртути и неона. Установлены: ФРЭЭ, транспортные характеристики, удельные потери мощности разряда на электронные процессы, концентрация и температура электронов, константы скоростей процессов упругого и неупругого рассеяния электронов на компонентах рабочей смеси в зависимости от величины приведенной напряженности электрического поля.